Управління конкурентоспроможністю компанії шляхом підвищення ефективності асортиментної політики в сучасних ринкових умовах - Мащенко, Марина Анатоліївна; Сергієнко, Олена Андріанівна; Гудименко, Вячеслав Павлович (Причорноморський науково-дослідний інститут економіки та інновацій, 2024)
У роботі розглянуто економічну сутність та здійснено класифікацію факторів конкурентоспроможності підприємства; розглянуто поняття асортиментної політики та її роль у забезпеченні конкурентоспроможності підприємства; запропоновано інструментарій оцінки та аналізу рівня конкурентоспроможності підприємства; розглянуто методи оцінки ефективності асортиментної політики в сучасних ринкових умовах; запропоновано концептуальну модель оцінки конкурентоспроможності асортиментної політики підприємства; здійснено оцінку конкурентних варіантів асортиментної політики з використанням кластерного аналізу; здійснено розпізнавання конкурентної асортиментної політики на основі методів дискримінантного аналізу

The object of the research is the processes of increasing the competitiveness of the enterprise through assortment management. The purpose of the work is to improve the company's competitiveness management mechanisms by increasing the effectiveness of the assortment policy. The work considered the economic essence and carried out the classifiation of factors of the enterprise's competitiveness; the concept of assortment policy and its role in ensuring the competitiveness of the enterprise are considered; a toolkit for assessing and analyzing the level of competitiveness of the enterprise is proposed; methods of assessing the effectiveness of assortment policy in modern market conditions are considered; a conceptual model for assessing the competitiveness of the company's assortment policy is proposed; an assessment of competitive variants of the assortment policy was carried out using cluster analysis; recognition of the competitive assortment policy based on the methods of discriminant analysis was carried out. The study delves into the processes of enhancing enterprise competitiveness through assortment management. The main objective is to refie the company's competitiveness management mechanisms, specifially by augmenting the effectiveness of the assortment policy. The research encompasses an exploration of the economic essence, classifiation of competitiveness factors, analysis of the assortment policy's role, introduction of a toolkit for assessing competitiveness, examination of methods for evaluating assortment policy effectiveness, proposal of a conceptual model for competitiveness assessment, and utilization of cluster and discriminant analysis for evaluating competitive assortment policy variants. The fidings are applicable to industrial enterprises, aiding in the formulation and substantiation of competitiveness management policies. Additionally, the study provides valuable insights into the economic foundations of competitiveness, offering a comprehensive classifiation of factors inflencing an enterprise's competitive edge. The conceptual model proposed serves as a strategic guide for assessing and optimizing the assortment policy, ensuring alignment with modern market conditions. By introducing a robust toolkit for competitiveness assessment, the research equips industrial enterprises with practical methods to analyze and enhance their competitive position. The utilization of cluster analysis enables a nuanced evaluation of competitive variants within the assortment policy, facilitating informed decision-making. Furthermore, the application of discriminant analysis contributes to recognizing competitive assortment policies, providing a systematic approach to identifying optimal strategies. These results collectively contribute to the development of a sophisticated competitiveness management policy, empowering industrial enterprises to navigate dynamic market landscapes successfully. In conclusion, the outcomes of this research offer a structured framework and practical tools for enterprises to elevate their competitiveness through effective assortment management, fostering strategic decision-making and sustainable growth. The results can be implemented in the activities of industrial enterprises for the formation and justifiation of competitiveness management policy.
Enhancing company competitiveness through improved assortment policy efficiency in modern market conditions
Keywords: конкурентоспроможність; метод; асортиментна політика; кластерний аналіз; розпізнавання; управління; модель; competitiveness; method; assortment policy; cluster analysis; recognition; management